IMPLEMENTASI PENYUSUNAN RENCANA KERJA DAN ANGGARAN BELANJA KEMENTERIAN PERTANIAN SEKTOR PERTANIAN TAHUN 2005-2012 - Aprilia Sukmawati; Hermanto Siregar; Nunung Nuryartono (School of Business, Bogor Agricultural University (SB-IPB), 2013)
ABSTRACTThe research objectives were to 1) analyze the implementation suitability of RKA-K/L document preparation which is implemented by Ministry of Agriculture with the concept of unified budget, Performance Base Budgeting (PBB) and Medium Term Expenditure Framework (MTEF) by using gap analysis method and 2) analyze the influence of expenditure in research, development and agriculture extension program; agriculture infrastructure; and increasing of production and agricultural productivity program, as well as agricultural subsidies to Gross Domestic Product (GDP) growth through multiple regression analysis. The methods used were gap analysis and multiple regression analysis. Gap analysis shows that there are still some obstacles in the application of unified budget concept, PBK and KPJM which resulted partial gap with applicable regulations. Multiple regression analysis shows that the Ministry of Agriculture budget expenditure both agriculture research, development and extension programs also agricultural production and productivity program had significant negative effect on the growth of GDP in agriculture sector. Therefore the government needs to pay attention to the government budget allocation which is closely related to the implementation of the existing programs in the Ministry of Agriculture.Keywords: government expenditure, sector of agriculture, ministry of agriculture, gap analysis, multiple regression analysisABSTRAKPenelitian ini bertujuan 1) menganalisis kesesuaian dokumen Rencana Kerja dan Anggaran Kementerian Negara/Lembaga (RKAK/L) yang disusun oleh Kementerian Pertanian dengan konsep penganggaran terpadu, Penganggaran Berbasis Kinerja (PBK) dan Kerangka Pengeluaran Jangka Menengah (KPJM) serta 2) menganalisis pengaruh alokasi anggaran untuk program penelitian dan penyuluhan pertanian; program infrastruktur pertanian; program peningkatan produksi dan produktivitas pertanian; serta subsidi benih dan pupuk terhadap pertumbuhan PDB. Metode analisis yang digunakan adalah analisis gap dan analisis regresi berganda. Hasil analisis gap menunjukkan bahwa masih ada beberapa kendala dalam penerapan konsep penganggaran terpadu, PBK dan KPJM yang mengakibatkan kesenjangan parsial dengan ketentuan yang berlaku, sedangkan hasil analisis regresi berganda menunjukkan bahwa alokasi anggaran Kementerian Pertanian untuk program penelitian pertanian, pengembangan dan penyuluhan serta program peningkatan produksi dan produktivitas pertanian berpengaruh negatif secara signifikan terhadap pertumbuhan PDB di sektor pertanian. Jadi pemerintah perlu memperhatikan alokasi anggaran pemerintah yang terkait erat dengan pelaksanaan program yang ada di Kementerian Pertanian.Kata kunci: anggaran belanja, sektor pertanian, kementerian pertanian, analisis gap, regresi berganda